PENINGKATAN KOMPETENSI PEDAGOGIK MERANCANG PROGRAM PENGAYAAN GURU SDN 4 JIKEN MELALUI SUPERVISI AKADEMIK TEKNIK PENILAIAN DIRI SENDIRI SEMESTER II TAHUN PELAJARAN 2018/2019 - Pujiati, Pujiati (UNIVERSITAS SLAMET RIYADI, 2019)
AbstractThe purpose of this research is to analyze the increasing of the teachersâ€™ pedagogical competencies in designing the enrichment program through academic supervision with self assessment on the second semester of the 2018/2019 year academic. This research is a School Action Research (SAR). The location of this research is Elementary School of 4 Jiken, Sub district of Jiken, Regency of Blora. The time of this research is early the first Semester of the 2018/2019 year academic. The subjects of this research are six class teachers (CT) and three subject teachers (ST). Technique of collecting data of this research is non test technique. The instruments of collecting data of this research are the sheets of self assessment, the sheets of observation and documentation. Technique of analyzing data of this research is comparative description. The procedure of this research is using Cycle Model. This research is going on two cycles. The results of this research are 1) pedagogical competencies in designing the enrichment program are increasing lack of competent category (D) become competent category (B) dan pedagogical competencies in designing the enrichment program including in competent category are increasing from 0% on the Early Condition become 22,23% on the First Cycle and 88,88% on the Second Cycle.Keywords: Pedagogical Competencies, The Enrichment Program, Academic Supervision, Self AssessmentAbstrakTujuan penelitian ini adalah menganalisis peningkatan kompetensi pedagogik merancang program pengayaan Guru SDN 4 Jiken melalui supervisi akademik teknik penilaian diri sendiri Semester II Tahun Pelajaran 2018/2019. Penelitian ini termasuk dalam jenis Penelitian Tindakan Sekolah (PTS). Tempat penelitian di SDN 4 Jiken, Kecamatan Jiken, Kabupaten Blora. Waktu penelitian pada awal Semester II Tahun Pelajaran 2018/2019. Subjek penelitian adalah enam Guru Kelas (GK) dan tiga Guru Pelajaran (GP). Teknik pengumpulan data penelitian ini dengan teknik nontes. Alat pengumpulan data penelitian ini dengan lembar penilaian diri sendiri, lembar pengamatan dan dokumentasi. Teknik analisis data penelitian ini adalah deskriptif komparatif. Prosedur penelitian ini menggunakan Model Siklus. Penelitian selama dua siklus. Hasil penelitian ini adalah 1) kompetensi pedagogik merancang program pengayaan meningkat dari kategori kurang berkompeten (D) menjadi kategori berkompeten (B) dan 2) kompetensi pedagogik merancang program pengayaan yang termasuk kategori berkompeten (B) meningkat dari 0% pada Kondisi Awal menjadi 22,23% pada Siklus I dan 88,88% pada Siklus II.Â Kata Kunci: Kompetensi Pedagogik, Program Pengayaan, Supervisi Akademik, Penilaian Diri Sendiri.